Epstein-Barr virus nuclear antigen 2 transactivates the long terminal repeat of human immunodeficiency virus type 1. - Scala, G (1993)
Human immunodeficiency virus type 1 (HIV-1)-infected subjects show a high incidence of Epstein-Barr virus (EBV) infection. This suggests that EBV may function as a cofactor that affects HIV-1 activation and may play a major role in the progression of AIDS. To test this hypothesis, we generated two EBV-negative human B-cell lines that stably express the EBNA2 gene of EBV. These EBNA2-positive cell lines were transiently transfected with plasmids that carry either the wild type or deletion mutants of the HIV-1 long terminal repeat (LTR) fused to the chloramphenicol acetyltransferase (CAT) gene. There was a consistently higher HIV-1 LTR activation in EBNA2-expressing cells than in control cells, which suggested that EBNA2 proteins could activate the HIV-1 promoter, possibly by inducing nuclear factors binding to HIV-1 cis-regulatory sequences. To test this possibility, we used CAT-based plasmids carrying deletions of the NF-kappa B (pNFA-CAT), Sp1 (pSpA-CAT), or TAR (pTAR-CAT) region of the HIV-1 LTR and retardation assays in which nuclear proteins from EBNA2-expressing cells were challenged with oligonucleotides encompassing the NF-kappa B or Sp1 region of the HIV-1 LTR. We found that both the NF-kappa B and the Sp1 sites of the HIV-1 LTR are necessary for EBNA2 transactivation and that increased expression resulted from the induction of NF-kappa B-like factors. Moreover, experiments with the TAR-deleted pTAR-CAT and with the tat-expressing pAR-TAT plasmids indicated that endogenous Tat-like proteins could participate in EBNA2-mediated activation of the HIV-1 LTR and that EBNA2 proteins can synergize with the viral tat transactivator. Transfection experiments with plasmids expressing the EBNA1, EBNA3, and EBNALP genes did not cause a significant HIV-1 LTR activation. Thus, it appears that among the latent EBV genes tested, EBNA2 was the only EBV gene active on the HIV-1 LTR. The transactivation function of EBNA2 was also observed in the HeLa epithelial cell line, which suggests that EBV and HIV-1 infection of non-B cells may result in HIV-1 promoter activation. Therefore, a specific gene product of EBV, EBNA2, can transactivate HIV-1 and possibly contribute to the clinical progression of AIDS.